Biological and pharmacological activities of amaryllidaceae alkaloids. Issue 21 (6th March 2015) - He, Maomao; Qu, Chunrong; Gao, Oude; Hu, Xianming; Hong, Xuechuan
<x xml:space="preserve">Abstract</x> This review discusses the recent developments on biological and pharmacological activities of amaryllidaceae alkaloids with IC50 or EC50 values since 2005, supporting the potential therapeutic possibilities for the use of these compounds.